Optimasi Kecepatan dan Waktu Pencampuran dalam Pembuatan Emulgel Ekstrak Teh Hijau - AGATHA BUDI SUSIANA LESTARI (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
The aims of the research are to determine the Significant effect factor among mixmg rate, mixing time and their interaction on the physical properties and stability of green tea emulgel and to determine the optimum composition area which can produce good emulgel. In our previous investigation was determined the optimum composition between emulsifying agent (Tween 80 and Span 80) and gelling agent (Carbopol) This research determined the optimum mixing process, particularly on mixing rate and mixing time usig the factorial design with two factors (mixing rate and mixing time) and two levels (high level and low level). The physical properties and stability parameter investigated were including viscosity, spreading ability and viscosity shift atter storage at predetermined temperature and humidity for a month. The results showed that mixing rate Significantly influence on the viscosity and spreading ability and the mixing time significantly influence on the Viscosity shift. The optimum composttion area was not produced because the factorial design equation for viscosity respond and viscosity shin were not significant so can not be used to predict responds.